Perceived Barriers to Blood Flow Restriction Training - Rolnick, Nicholas; Kimbrell, Kyle; Cerqueira, Mikhail Santos; Weatherford, Ben; Brandner, Christopher (Frontiers in Rehabilitation Sciences, 2021)
Blood flow restriction (BFR) training is increasing in popularity in the fitness and rehabilitation settings due to its role in optimizing muscle mass and strength as well as cardiovascular capacity, function, and a host of other benefits. However, despite the interest in this area of research, there are likely some perceived barriers that practitioners must overcome to effectively implement this modality into practice. These barriers include determining appropriate BFR training pressures, access to appropriate BFR training technologies for relevant demographics based on the current evidence, a comprehensive and systematic approach to medical screening for safe practice and strategies to mitigate excessive perceptual demands of BFR training to foster long-term compliance. This manuscript attempts to discuss each of these barriers and provides evidence-based strategies and direction to guide clinical practice and future research.